SOCIAL MEDIA USAGE AND UNDERGRADUATES’ WRITING SKILLS, THE MEETING POINT: A CASE STUDY OF THE UNIVERSITY OF ILORIN AND BAMIDELE OLUMILUA UNIVERSITY OF EDUCATION, SCIENCE AND TECHNOLOGY, IKERE EKITI - Felicia Tomi OBADARE (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study has explored how the use of social media has impacted on the writing skills of undergraduates in University of Ilorin and Bamidele Olumilua University of Education, Science and Technology, Ikere Ekiti (BOUESTI). The study design was descriptive survey and simple random sampling was applied to undergraduates by the administration of a structured questionnaire. The data was analyzied using weighted mean scores and standard deviations. The findings indicated that the overall social media usage among the students was high with a cluster mean outcome of 3.16. This implied that they utilised applications such as WhatsApp, Facebook, Instagram, and Twitter, both at school and during leisure. The research established that social media influenced certain writing abilities, and the cluster mean was 3.18. As one case in point, social media has an effect on spelling (mean = 3.52), academic tone (mean = 3.48), and transfer of informal punctuation patterns (mean = 3.01). The influence on abbreviations and sentence structure was however not very strong. The research also established that social media has a positive impact on the writing development of the students with a cluster mean of 3.07. Students agreed that social media enhances fluency in writing (mean = 3.41), enhances vocabulary (mean = 3.02), understandability of language (mean = 2.85), and creativity (mean = 3.11). Despite these negatve influences were also identified The negative effects cluster average of 2.99 suggests moderate concerns, including the use of abbreviations in academic writing (mean = 3.01), the reduced concentration on spelling (mean = 3.11), and the challenges with punctuation (mean = 3.00); the lack of grammar decline, however, could not be strongly supported. The research proposes the integration of digital literacy into writing education, promotion of esponsible use of social media, and the strengthening of systems to support writing in universities.